Occurrence Download - GBIF.Org User (The Global Biodiversity Information Facility, 2016)
A dataset containing 5943 species occurrences available in GBIF matching the query: { "and" : [ "TaxonKey is Chelonia mydas (Linnaeus, 1758)", "HasCoordinate is true" ] } The dataset includes 5943 records from 65 constituent datasets; see https://api.gbif.org/v1/occurrence/download/0001849-160311141623029/datasets/export for details. Data from some individual datasets included in this download may be licensed under less restrictive terms.
Keywords: GBIF; biodiversity; species occurrences